Market Socialism. Government preference or individual preferences? A reply to Mauricio Ramírez-Gómez (Polis (Santiago), 2018)
The interesting contribution of Prof. Ramirez-Gomez deals with the role that the market must have in a democratic society, and with this intention, suggests that market should respond to government’s preferences rather than individual preferences. Our friendly reply states that this argument must be extended in order to avoid interpretations that will mistake it with formulas experienced by the central planification economies, which have shown their inefficiency in the provision of pertinent use-values. In this sense, we maintain that the market must be subordinated to the individual preferences facilitating the freedom of the people in choosing  investment alternatives and consumption, until the point in which such exercise can only  be held through the reduction of a reasonable exercise of freedom of the others.
Keywords: market socialism; democracy; welfare; planning; austro-liberalism